Compact UWB bandpass filter with a reconfigurable notched band. Issue 4 (29th November 2017) - Hua, Changzhou; Lu, Yunlong
Abstract: This article presents a design of compact ultra‐wideband (UWB) bandpass filter with a narrow notched band. The UWB frequency responses are achieved by using a microstrip–CPW broadside coupling structure. And a pair of side‐coupled short‐circuited microstrip lines is introduced to generate a narrow notched band. Based on this design, by loading a pair of varactor diodes at the end of the side‐coupled short‐circuited microstrip lines, a reconfigurable notched‐band UWB filter can also be obtained, which can avoid the existing interferences such as 5.8 GHz wireless local‐area network signals and 6.8 GHz RF identification communication systems signals and in the UWB frequency range. Commercial software ANSYS HFSS is used to analyze and design this filter. Simulated results show that it has good filtering performances, compact size, and notched‐band reconfigurability.